2010
DOI: 10.1007/s10765-010-0857-y
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Test on Thermophysical Properties of the ITER Grade Heat Sink Material Copper–Chromium–Zirconium

Abstract: Copper-chromium-zirconium (CuCrZr) is a commercially available, precipitationstrengthened alloy. The combination of its good thermal conductivity and mechanical strength at low and moderate temperatures made it of interest for use as heat sink material in high heat flux components in actual and future fusion facilities. Its drawback is the microstructural modification and thereby particularly the loss of mechanical strength at temperatures above 500 °C. This limits allowable operational temperatures and also l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Pintsuk et al [40] have reported a thorough investigation on the thermo-physical properties, namely "Interlaboratory tests", where eight European laboratories and a company Netzsch as an external reference laboratory have took part in, to perform thermo-physical tests on specimens from the same batch of material. The material for this "Interlaboratory tests" was taken from a bar material (35×35×1000mm 3 ) produced by the company Zollern/Laucherthal [41].…”
Section: Thermo-physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pintsuk et al [40] have reported a thorough investigation on the thermo-physical properties, namely "Interlaboratory tests", where eight European laboratories and a company Netzsch as an external reference laboratory have took part in, to perform thermo-physical tests on specimens from the same batch of material. The material for this "Interlaboratory tests" was taken from a bar material (35×35×1000mm 3 ) produced by the company Zollern/Laucherthal [41].…”
Section: Thermo-physical Propertiesmentioning
confidence: 99%
“…7 Thermal conductivities versus temperatures. [1,14,29,40,42,43] Fig. 7 shows average thermal conductivity values as well as values from various laboratories in the "Interlaboratory tests".…”
Section: Thermo-physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The divertor was simulated at both 10MW/m 2 and 20MW/m 2 as well as investigating the influence of the performance with and without tape as well as with increased twist ratio. Each material within the system has its own operating limit and for the CuCrZr pipe this limit is 773K [58].…”
Section: Resultsmentioning
confidence: 99%
“…This might happen because after infiltration, it was probably in the unstable state—either in a homogenized or partially aged state. The fully homogenized alloy shows the RT thermal conductivity at the level of 170 W/m K 30 and typical aged one has the conductivity in the range of 290–330 W/m K. 30,39 The microstructure remains homogenized only in the case if water quenching (cooling speed of 90°C/s) is applied after homogenization treatment. Our CuCrZr alloy was cooled certainly at a smaller speed that is estimated to 3–5 °C/s and it resulted to not perfectly homogenized state, although, precipitates were not observed.…”
Section: Discussionmentioning
confidence: 99%